PENGEMBANGAN SISTEM INFORMASI PERJALANAN DINAS BERBASIS WEB UNTUK EFISIENSI PENGELOLAAN BIAYA PADA INSTANSI PEMERINTAH - Dendy Kurniawan; Ayuk Nurmala (LPPM Politeknik Pratama Kendal, 2026)
The management of official travel in government institutions requires a structured and efficient system, particularly in cost management. However, in practice, many institutions still rely on manual or semi-computerized processes, which may lead to data recording errors, reporting delays, and low efficiency in data management. This study aims to develop a web-based official travel information system to improve cost management efficiency in government institutions. The research method used is Research and Development (R&D), which includes requirement analysis, system design using Unified Modeling Language (UML), system development using PHP and MySQL, and system testing through Black Box Testing and User Acceptance Test (UAT). The results indicate that the developed system is capable of integrating the entire official travel management process, from data entry to report generation. The system significantly improves time efficiency, data accuracy, and ease of cost management and reporting. Furthermore, it enhances transparency and cost control within the organization. Therefore, the proposed web-based information system can serve as an effective solution to support digital transformation and improve financial management quality in government institutions.